PENGEMBANGAN SISTEM PENDUKUNG KE BEASISWA UNGGULAN DI SMK PRIMA UNGGUL MENGGUNAKAN METODE VIKOR DENGAN PERTIMBANGAN FAKTOR AKADEMIK, EKONOMI, DAN POTENSI: Penulis: Robby Adiyasa Putra, Dosen: Mochamad Adhari Adiguna, S.ST., M.Kom. - Robby, ROBBY ADIYASA PUTRA (JUPIK : Jurnal Penelitian Ilmu komputer, 2025)
This study develops a web-based decision support system for scholarship selection at the vocational high school level using the VIKOR method, a Multi-Criteria Decision Making (MCDM) approach focused on compromise solutions. The system evaluates three key criteria: academic performance, economic condition, and student potential. Developed with Laravel PHP framework and MySQL using the Rapid Application Development (RAD) model, the system enables quick prototyping and user-centered adaptation. It integrates essential DSS components—Database, decision model, and User Interface—to support a more transparent, fair, and accountable selection process. Results indicate that alternative A24 consistently ranks first based on Qi, Si, and Ri scores, meeting the Acceptable Stability in Decision Making under varying v values: Voting by Majority Rule (v = 0.7), By Consensus (v = 0.5), and With Veto (v = 0.3).